DEVELOPMENT TENDENCIES OF THE FIELD OF EDUCATION UNDER THE CONDITIONS OF FORMING THE KNOWLEDGE ECONOMY (Marketing Journal, 2025)
In this article, the knowledge economy system affecting the sustainable economic development of our country is studied. The conditions in the formation of the knowledge economy in our country were analyzed and conclusions were drawn.
Keywords: Education; knowledge economy; trend; technology; region; labor markets; modern knowledge